2013
DOI: 10.1097/mlr.0b013e31829c8ca4
|View full text |Cite
|
Sign up to set email alerts
|

Differential Receipt of Sentinel Lymph Node Biopsy Within Practice-based Research Networks

Abstract: Background Provider-based research networks (PBRNs) are promising for accelerating not only research, but also dissemination of research-based evidence into broader community practice. Sentinel lymph node biopsy (SLNB) is an innovation in breast cancer care associated with equivalent survival and lower morbidity, as compared to standard axillary lymph node dissection. We examined the diffusion of SLNB into practice and whether affiliation with the Community Clinical Oncology Program (CCOP), a cancer-focused PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The current results and those reported by Meyer et al (2013), suggest that one way to reduce disparities in cancer treatment, specifically related to receipt of innovative treatments and technologies, may be to improve access to these treatments for minority patients living in the South, areas that have a high proportion of minority patients, or receiving treatment in organizations that were found to slowly adopt new treatment technology. Operationalizing this concept has always been challenging.…”
Section: Discussionmentioning
confidence: 50%
“…The current results and those reported by Meyer et al (2013), suggest that one way to reduce disparities in cancer treatment, specifically related to receipt of innovative treatments and technologies, may be to improve access to these treatments for minority patients living in the South, areas that have a high proportion of minority patients, or receiving treatment in organizations that were found to slowly adopt new treatment technology. Operationalizing this concept has always been challenging.…”
Section: Discussionmentioning
confidence: 50%
“…Moreover, there is growing evidence of their effectiveness in facilitating the diffusion of trial-proven interventions to broader populations. For example, in the context of colorectal cancer, PBRNs have been associated with patients having a greater probability of receiving innovative cancer care [7, 8]. We previously reported on a novel statewide system for ongoing monitoring and public reporting of NCI clinical trial enrollment, developed to extend clinical trials access to broader patient populations [3].…”
Section: Introductionmentioning
confidence: 99%
“…We and others have noted slower adoption and lower rates of sentinel lymph node biopsy, an innovative morbidity-sparing surgical procedure, among eligible Black women compared to Whites,(21,22) and these differences are partially explained by the concentration of White patients within National Cancer Institute (NCI)-designated comprehensive cancer centers, hospitals with high breast cancer volume, greater affiliation with research cooperative groups and the American College of Surgeons Oncology Group (ACOSOG), and the NCI’s Comprehensive Community Oncology Program (CCOP). (23,24) Breast reconstruction is also less utilized by minority women, which appears to be related to lower access to plastic surgeons. (25) Interestingly, one large study showed that Black women were less actively involved in choosing their surgeon or hospital for breast surgery.…”
Section: Disparities In the Usmentioning
confidence: 99%